2019
DOI: 10.1111/jeb.13545
|View full text |Cite
|
Sign up to set email alerts
|

When mother knows best: A population genetic model of transgenerational versus intragenerational plasticity

Abstract: Many organisms exhibit phenotypic plasticity; producing alternate phenotypes depending on the environment. Individuals can be plastic (intragenerational or direct plasticity), wherein individuals of the same genotype produce different phenotypes in response to the environments they experience. Alternatively, an individual's phenotype may be under the control of its parents, usually the mother (transgenerational or indirect plasticity), so that mother's genotype determines the phenotype produced by a given geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 65 publications
(80 reference statements)
2
28
0
Order By: Relevance
“…Social dominance hierarchies take days to weeks to be established (Nelson, Colson, et al, ; Nelson, Cunningham, Ruff, & Potts, ), and we find that signals about paternal rank can be transmitted to offspring on this timescale. Once established, we found that dominance persists for several weeks, and is subject to a relatively low turnover rate, suggesting that a father's current social status is predictive of the environment his offspring will be born in—thus satisfying one of the predictions for the evolution of parental effects (DeWitt et al, ; Dury & Wade, ).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Social dominance hierarchies take days to weeks to be established (Nelson, Colson, et al, ; Nelson, Cunningham, Ruff, & Potts, ), and we find that signals about paternal rank can be transmitted to offspring on this timescale. Once established, we found that dominance persists for several weeks, and is subject to a relatively low turnover rate, suggesting that a father's current social status is predictive of the environment his offspring will be born in—thus satisfying one of the predictions for the evolution of parental effects (DeWitt et al, ; Dury & Wade, ).…”
Section: Discussionsupporting
confidence: 66%
“…Phenotypic plasticity is an important source of behavioural and morphological variation in natural populations and occurs over short and long timescales (Dury & Wade, ). On short timescales, intragenerational phenotypic plasticity is the ability of an individual to produce alternative phenotypes from the same genotype depending on environmental conditions (DeWitt & Scheiner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent genetic and mathematical models of WGP, TGP and their possible coexistence predict that the two types of plasticity can operate either separately or additively, depending on the environmental conditions (Lande, 2009;Ezard et al, 2014;Leimar and McNamara, 2015;Dury and Wade, 2019). Empirical support for this has been found in both plants and animals (Agrawal et al, 1999;Sultan et al, 2009;Mikulski and Pijanowska, 2010;Walsh et al, 2015Walsh et al, , 2016Katoh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Predictive models have indicated that both WGP and TGP are favoured by spatial and temporal environmental heterogeneity, environmental cues that are reliable predictors of upcoming environmental conditions, and low costs of plasticity (Uller, 2008;Bonduriansky et al, 2012;Dury and Wade, 2019). However, there are differences in the theoretical frameworks regarding the kinds of conditions that favour WGP, TGP and their possible co-occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…2013; but see also Donelan and Trussell 2018). Moreover, adaptive maternal effects are expected to evolve when environmental conditions differ across generations, when there are reliable cues about offspring environment, and if the cost of cue detection by the offspring is low, and if there is no or low levels of intergenerational conflict to maximize fitness (Mousseau and Fox 1998b;Marshall and Uller 2007;Kuijper and Hoyle 2015;Dury and Wade 2019). However, despite clear theoretical predictions for parental effects to evolve in response to local environmental conditions, there is limited empirical knowledge on the evolution of parental effects across varying environmental conditions (but see Dey et al 2016;Lind et al 2019).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%